Engineering and technical design of main streets with integration of green infrastructure elements - E. Yu. Zaykova; S. S. Feofanova (Vestnik MGSU)
Introduction. Climatic characteristics are of key importance in modern urban planning practice. The increase in precipitation ‘challenges’ outdated normative documents. In order to increase the adaptive capacity of cities to climate warming in the 80s of the XX century, Western specialists proposed the use of green infrastructure (GIF). In the regulatory documents of the Russian Federation, the concept that would include the application of science and mathematics to resolve the problem of flooding urban spaces does not yet exist. The authors offer their own vision of solving this problem.Materials and methods. The author’s definition of “engineering and technical design” is given, the difference between the existing types of action in the urban environment is indicated, and the main stages of implementation are highlighted. The authors found that urban areas in Moscow that are often flooded by stormwater are main streets of the 2nd class of regulated traffic in the western administrative district. An urban planning analysis of the study area was carried out taking into account climatic characteristics, and the role of “green infrastructure” and bioengineering structures was also identified.Results. The author’s calculation of the average flow rate of stormwater in a bioengineered structure is necessary to select the size of the elements of the green infrastructure that are planned to be placed on the territory. The flow rate of stormwater over an impenetrable surface is almost three times higher than with soil and vegetation resistance, depending on the slope of the territory.Conclusions. The variant of the implementation of engineering and technical design on the main street of Moscow — Michurinsky Prospekt, which includes the design idea of space using the structure of man–made biotopes, is offered. Storm water is accumulated and redistributed through bioengineered structures, feeding vegetation.